Management of Self-Efficiency Management and Work Commitment at the School of the Cooperation Agreement Unit - Murniarti, Erni; Sihotang, Hotmaulina; Purba, Santri Chintia (Advances in Social Sciences Research Journal, 2022)
This study aims to reveal factors (1) reveal the dominant factors of self-efficacy and describe the characteristics of self-efficacy; (2) reveal the dominant factor of work commitment and describe the characteristics of work commitment; (3) reveal whether there is a teacher’s self-efficacy, and work commitment based on gender; (4) reveal whether there are differences in self-efficacy and work commitment based on educational qualifications; (5) reveal whether there are differences in self-efficacy and work commitment based on work period. The study used a quantitative approach with a survey method with factor analysis using SPSS 26, and the study population was all SPK school teachers and a sample of 258 people with the purposive sampling technique. Data was obtained through a questionnaire. Data analysis used factor analysis to determine the dominant factors of self-efficacy and work commitment variables. The difference test uses the Tukey test. The results showed that the dominant factor of self-efficacy is the ability to solve problems, and the dominant factor of work commitment is working continuously. In addition, it was found that there was no difference in teacher self-efficacy and work commitment based on educational qualifications and gender. The longer the teacher works, the more self-efficacy and work commitment increase.